A numerical study of the impact of vegetation on mean and turbulence fields in a European-city neighbourhood. (December 2020) - Barbano, Francesco; Di Sabatino, Silvana; Stoll, Rob; Pardyjak, Eric R.
Abstract: Vegetation in the urban environment has various impacts on microclimate. While optimal strategies for investigating these impacts are the subject of ongoing research, most approach rely on Computational Fluid Dynamics (CFD) simulations. We evaluate mean wind and turbulence fields simulated using the fast-running Quick Urban & Industrial Complex (QUIC) Dispersion Modeling System, a simplified CFD tool that resolves buildings and vegetation. We use QUIC to investigate the role of deciduous trees in modifying the airflow of a real neighbourhood in Bologna, Italy by running large ensembles of simulations per case study, obtained by varying the input wind direction. This approach can minimise intrinsic model uncertainty as well as uncertainties associated with real environments. Model validation is performed using measurements from an experimental field campaign focused on a vegetated urban street canyon in Bologna. Ensemble simulation results show good agreement with the experimental data for various conditions (i.e., simulation ensembles overlap experimental variability in most cases). The role of trees is investigated by comparing simulations with and without trees. Trees are found to reduce airflow by constraining local circulation and reducing turbulence intensity. Finally, the combined effect of building morphology and vegetation is investigated by adopting a formalism to represent the presence of vegetation using area-fraction coefficients. An area-fraction coefficient threshold of 0.225 has been identified that separates flow behaviours and is present in cases with and without vegetation. Below this threshold, a constant wind and turbulence regime exists, while above the threshold, winds and turbulence vary with area-fraction coefficient. Highlights: Ensemble simulation methodology to evaluate and validate mean and turbulence fields. Probability distribution-based methodology to evaluate the impact of vegetation. Morphological analysis using area-fraction distributions that include vegetation. Vegetation constrains and reduces the intensity of the local circulation. Two flow regimes are identified are identified as function of morphology density.